Steel plates for hot stamping and hot stamping parts

A surface treatment film with high emissivity on steel plates allows for differential temperature control during hot stamping, addressing economic and robustness issues in producing steel parts with varying strengths.

JP7620241B2Active Publication Date: 2025-01-23NIPPON STEEL CORPORATION
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023512605
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-04-08
Publication Date
2025-01-23
Estimated Expiration
2041-04-08

AI Technical Summary

Technical Problem

Existing methods for manufacturing steel parts with varying strengths through hot stamping are economically disadvantageous and lack manufacturing robustness, as they require multiple steel plates or complex cooling molds.

Method used

Applying a surface treatment film with high emissivity to selected areas of a steel plate to create differential temperature increase rates during hot stamping, allowing for regions with different strengths without the need for multiple steel plates or complex cooling molds.

Benefits of technology

Enables the production of steel parts with distinct strength variations by controlling temperature rise and hardenability, reducing manufacturing complexity and costs while maintaining product robustness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007620241000007
    Figure 0007620241000007
  • Figure 0007620241000008
    Figure 0007620241000008
  • Figure 0007620241000001
    Figure 0007620241000001
Patent Text Reader

Abstract

This steel sheet for hot stamping has, on a surface thereof: a portion that has a surface treatment coating film demonstrating an emissivity of 60% or more at a wavelength of 8.0 µm at 25°C; and a portion that does not have the surface treatment coating film. The surface treatment coating film contains carbon black and at least one oxide selected from the group consisting of Zr oxide, Zn oxide and Ti oxide. The carbon black and the oxide are dispersed throughout the entirety of the surface treatment coating film. The surface treatment coating film has a silica content of 0-0.3 g / m2. When the adhesion amounts of the carbon black and the oxide are XCB (g / m2) and XOxide (g / m2), respectively, the following formulas are satisfied. 118.9 ≤ × ≤ 24280 / {6700 / (100 + 76 × XCB) + 18000 / (130 + 65 × XOxide)} ≤ 332.0
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a steel sheet for hot stamping and a hot stamped member. [Background technology]

[0002] In recent years, there has been an increasing demand to reduce the consumption of chemical fuels in order to protect the environment and prevent global warming, and this demand is affecting various manufacturing industries. For example, automobiles, which are indispensable as a means of transportation in daily life and activities, are no exception, and there is a demand for improving fuel efficiency by reducing the weight of the vehicle body. However, in the case of automobiles, simply reducing the weight of the body may lead to a decrease in safety, and this is not acceptable in terms of product quality. Therefore, when reducing the weight of the body, it is necessary to ensure appropriate safety.

[0003] Many of the structures of automobiles are formed from iron, particularly steel plates, and reducing the weight of the steel plates is important for reducing the weight of the vehicle body. Such demands for steel plates are not limited to the automobile manufacturing industry, but are also made in various manufacturing industries. In order to meet such demands, it is possible to simply reduce the weight of the steel plates by reducing the thickness of the steel plates. However, reducing the thickness of the steel plates leads to a decrease in the strength of the structures. For this reason, in recent years, research and development has been conducted on steel plates that can maintain or increase the mechanical strength of structures made of the steel plates by increasing the mechanical strength of the steel plates, even if they are thinner than steel plates that were previously used.

[0004] Generally, materials with high mechanical strength tend to have poor shape fixability during forming such as bending. Therefore, when processing into a complex shape, the processing itself becomes difficult. One of the means for solving the problem of formability is the so-called "hot stamping method (also called hot pressing method, hot pressing method, high temperature pressing method, die quenching method)". In this hot stamping method, the material to be formed is heated to a high temperature to transform (austenitize) into a structure called austenite, and the steel plate softened by heating is pressed to form, and cooled after forming. According to this hot stamping method, the material is once heated to a high temperature to soften it, so that the material can be easily pressed. Furthermore, the mechanical strength of the material can be increased by the quenching effect caused by cooling after forming. Therefore, this hot stamping method can obtain a formed product with good shape fixability and high mechanical strength.

[0005] On the other hand, some parts are required to have both high and low strength parts. This is because, while high strength is necessary to protect personnel, parts other than those that need to protect personnel need to have relatively low strength in order to absorb energy during a collision.

[0006] From the above viewpoint, for example, Patent Document 1 below describes a part in which at least two types of Zn-based plated steel sheets having different steel components are joined. Patent Document 2 below describes a technique for creating different structures after cooling by varying the average cooling rate and cooling stop temperature depending on the location of the steel sheet. Patent Document 3 below describes a technique for improving ductility by tempering some locations after martensitic transformation by controlling the temperature of a mold. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] International Publication No. 2016 / 139953 [Patent Document 2] JP 2014-161854 A [Patent Document 3] JP 2016-41440 A Summary of the Invention [Problem to be solved by the invention]

[0008] However, in order to manufacture parts such as those described in Patent Document 1, it is necessary to manufacture steel plates with different strengths, which not only increases the manufacturing load but also requires a joining process, making it uneconomical.

[0009] Furthermore, using the method described in Patent Document 2 above is not preferable because it requires two types of cooling molds, which is economically disadvantageous and makes it difficult to ensure robustness in production.

[0010] Furthermore, even if the technique described in Patent Document 3 is used, it is difficult to ensure robustness in manufacturing, similar to Patent Document 2, and this is not preferable.

[0011] As described above, there is a demand for a technology that enables hot stamping while suppressing an increase in costs and ensuring the robustness of the product.

[0012] Therefore, the present invention has been made in consideration of the above problems, and an object of the present invention is to provide a steel sheet for hot stamping suitable for manufacturing a part having parts with different strengths by hot stamping, and a hot stamped member having parts with different strengths. [Means for solving the problem]

[0013] In order to solve the above problems and manufacture metal parts having parts with different strengths, the present inventors conducted extensive research and came up with the idea of ​​increasing the temperature rise rate (heating rate) by applying a high-emissivity surface treatment coating to part of the surface of a steel sheet.

[0014] By providing a surface treatment film that increases the emissivity to a part of the steel sheet, it is possible to provide a difference in the heating rate during hot stamp heating. In a hot stamping steel sheet having such characteristics, the part to which the film is provided is austenitized completely, and the other part is not austenitized when it is removed from the heating furnace and rapidly cooled by a die. As a result, a difference occurs in the hardenability between the part to which the film is provided and the other part, making it possible to manufacture parts made from the steel sheet having parts with different strengths.

[0015] The present invention has been made based on the above findings obtained by the present inventors, and the gist of the present invention is as follows.

[0016] [1] A steel sheet having a surface having a surface treatment film having an emissivity of 60% or more at 25°C at a wavelength of 8.0 μm and a surface not having the surface treatment film, the surface treatment film being composed of carbon black and Zr oxide. , and and one or more oxides selected from the group consisting of Ti oxides, and the carbon black and the oxides are present in a dispersed state throughout the surface treatment film, and the surface treatment film has a silica content of 0 to 0.3 g / m 2 The amount of the carbon black and the amount of the oxide are each X CB (g / m 2 ), X Oxide (g / m 2 ) a steel sheet for hot stamping, which satisfies the following formula (1): 118.9≦24280 / {6700 / (100+76×X CB )+18000 / (130+65×X Oxide )}≦332.0 ··· Formula (1) [2] The steel sheet for hot stamping according to [1], wherein the surface treatment film contains 5.0 to 40.0 vol. % of the carbon black and 1.0 to 30.0 vol. % of the oxide. [3] The amount of carbon black attached, X CB (g / m 2 ) and the amount of oxide attached X Oxide (g / m2 ) and the ratio X Oxide / X CB The steel sheet for hot stamping according to [1] or [2], wherein R is 0.20 or more and 200.00 or less. [4] The amount of carbon black attached X CB is 0.030g / m 2 or more, and the amount of adhesion of the oxide X Oxide is 0.030g / m 2 The steel sheet for hot stamping according to any one of [1] to [3] above. [5] The steel sheet for hot stamping according to any one of [1] to [4], wherein the emissivity of the surface treatment film at 700° C. at a wavelength of 8.0 μm is 60% or more. [6] The steel sheet for hot stamping according to any one of [1] to [5], wherein one or both sides of the steel sheet for hot stamping have a metal plating layer between a substrate of the steel sheet and the surface treatment film. [7] A steel sheet having a surface having a portion having a surface treatment film and a portion not having the surface treatment film, the surface treatment film being Zr oxide. , and and one or more oxides selected from the group consisting of Ti oxides, and the amount of the oxide deposited is X Oxide is 0.030g / m 2 or more, and the surface treatment film has a silica content of 0 to 0.3 g / m 2 A hot stamped component. [8] The hot stamped member according to [7], wherein, when a Vickers hardness defined in JIS Z 2244 (2009) is measured, a portion exhibiting a maximum hardness HVmax and a portion exhibiting a minimum hardness HVmin are present, and a hardness difference ΔHV between the maximum hardness HVmax and the minimum hardness HVmin is 150 or more. [9] The hot stamped member according to [8], wherein both the portion exhibiting the maximum hardness HVmax and the portion exhibiting the minimum hardness HVmin are present within a region composed of a common material. Effect of the Invention

[0017] As described above, according to the present invention, it is possible to provide a steel sheet for hot stamping suitable for manufacturing parts having portions with different strengths, and a hot stamped member having portions with different strengths. [Brief description of the drawings]

[0018] [Figure 1] FIG. 1 is a diagram showing a schematic diagram of the start and completion times of austenitization in a coated region and an uncoated region during hot stamp heating. [Diagram 2] FIG. 2 is a diagram showing a schematic diagram of a coated portion and its central portion (P1) and a non-coated portion and its central portion (P2) on the surface of a steel sheet for hot stamping. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] Hereinafter, preferred embodiments of the present invention will be described in detail with reference to the accompanying drawings.

[0020] (Steel sheets for hot stamping) The steel sheet for hot stamping according to the embodiment of the present invention described below is suitable for manufacturing parts having parts with different strengths. The steel sheet for hot stamping has a portion on the surface of the steel sheet that has a surface treatment film having an emissivity of 60% or more at a wavelength of 8.0 μm at 25° C., and a portion that does not have such a surface treatment film. In this embodiment, by providing a surface treatment film to a portion of the steel sheet as described above, the emissivity at a wavelength of 8.0 μm at 25° C. can be increased to 60% or more.

[0021] In the hot stamping steel sheet according to the present embodiment, the type of the steel sheet (base steel sheet) serving as the base material is not particularly limited. Examples of such steel sheets include various hot-rolled steel sheets, cold-rolled steel sheets, and plated steel sheets. Plated steel sheets include steel sheets that have been subjected to, for example, hot-dip aluminum plating, hot-dip galvanizing, alloyed hot-dip galvanizing, and electrolytic galvanization, but are not limited to these plated steel sheets as long as they are applicable to hot stamping.

[0022] Conventionally, most of the steel sheets used for automotive frame parts and the like have been hot-rolled steel sheets, cold-rolled steel sheets, or plated steel sheets coated with aluminum, zinc, etc. These steel sheets have low emissivity, so the heating rate in response to radiant heating with a wavelength of around 8.0 μm is low.

[0023] In this embodiment, a specific surface treatment coating is applied only to a part of the steel sheet surface, thereby increasing the heating rate of the coated portion during hot stamp heating, as shown in Fig. 1. After the coated portion reaches a temperature of the Ac3 point or higher and the non-coated portion reaches a temperature below the Ac3 point, the steel sheet is hot stamped, thereby making it possible to locally convert the coated portion into a quenched structure (martensite structure).

[0024] In this embodiment, a surface treatment film having a high emissivity is applied to a part of the surface of the steel sheet. Specific methods for applying the surface treatment film include painting and lamination, but are not limited to these methods. The above-mentioned surface treatment film may be applied to only one side of the steel sheet, or may be applied to both sides of the steel sheet. The emissivity at a wavelength of 8.0 μm at 25° C. of the area on the surface of the steel sheet to which the surface treatment film is applied is 60% or more. The emissivity at a wavelength of 8.0 μm at 25° C. of the area to which the surface treatment film is applied is preferably 70% or more, and more preferably 80% or more.

[0025] The emissivity can be measured according to the method described in the Japanese Industrial Standard JIS R 1801 (2002). In this case, a sample is placed in a Fourier transform infrared spectrophotometer, and the radiation intensity at a wavelength of 8.0 μm is measured at 25° C. to calculate the emissivity.

[0026] It is also possible to measure the radiation intensity of a target area at 25°C using a radiation thermometer set to a measurement wavelength of 8.0 µm, and calculate the emissivity from the ratio to the radiation intensity of a black body.

[0027] When applying a surface treatment film to only a part of the steel sheet surface by painting, for example, an organic or inorganic treatment liquid containing carbon black and a metal oxide is applied to a part of the steel sheet surface using a roll coater or curtain coater, and then the volatile components in the treatment liquid are dried to apply the surface treatment film. Alternatively, a coating can be applied to any part of the steel sheet surface by covering a part of the steel sheet with polyester tape or other material and then painting with the treatment liquid.

[0028] In particular, when coating using an inkjet, it is possible to apply the treatment liquid to any desired position with high precision, and it is also possible to continuously change the film thickness.

[0029] <Surface treatment film> In the hot stamping steel sheet according to the present embodiment, the emissivity at 25°C at a wavelength of 8.0 μm of the portion to which the surface treatment film is applied is 60% or more. When the emissivity at 25°C at a wavelength of 8.0 μm is less than 60%, the difference in the heating rate with respect to the portion to which the surface treatment film is not applied becomes small. As a result, the hardness difference after heating and cooling in hot stamping cannot be ensured, or the freedom of the timing of removing the steel sheet from the heating furnace to ensure the hardness is reduced, which places a burden on production, making it difficult to achieve both weight reduction and safety performance as an automobile part. The emissivity at 25°C at a wavelength of 8.0 μm is preferably 80% or more. By making the emissivity at 25°C at a wavelength of 8.0 μm 80% or more, it becomes easier to ensure the above-mentioned hardness difference and it becomes possible to further reduce the burden on production. The higher the emissivity at 25°C at a wavelength of 8.0 μm of the portion to which the surface treatment film is applied, the better, and the upper limit is not specified, and it may be 100%.

[0030] In order to achieve an emissivity of 60% or more at a wavelength of 8.0 μm at 25° C., the surface treatment film according to this embodiment contains carbon black and a specific metal oxide as described in detail below. The surface treatment film according to this embodiment may further contain a binder component and various additives, etc., as necessary. Furthermore, the surface treatment film according to this embodiment may not contain silica, or may contain silica within a certain range. By adjusting the contents of carbon black and metal oxide, etc., and the film thickness of the surface treatment film, it is possible to achieve a desired emissivity.

[0031] More specifically, the surface treatment film according to this embodiment contains carbon black and one or more oxides selected from the group consisting of Zr oxide, Zn oxide, and Ti oxide, and the carbon black and the oxides are dispersed throughout the surface treatment film. CB (g / m 2 ) and the amount of oxide attached is expressed as X Oxide (g / m 2 ), the surface treatment film according to this embodiment satisfies the relationship represented by the following formula (1).

[0032] 118.9≦24280 / {6700 / (100+76×X CB )+18000 / (130+65×X Oxide )}≦332.0 ··· Formula (1)

[0033] The above formula (1) defines the relationship between the rate of increase (%) of temperature rise (°C / s) and the amount of carbon black and oxides attached. More specifically, this formula stipulates that, with respect to the rate of increase of temperature rise, carbon black functions as a heat absorbing material in the range up to 700°C, and Zr oxide, Zn oxide, and Ti oxide remaining in this temperature range function as heat absorbing materials in the range of 700°C or higher.

[0034] As briefly mentioned above, the surface treatment film according to this embodiment can be formed by applying a treatment liquid containing carbon black and a specific oxide to a desired portion of a steel sheet. As a result, in the surface treatment film according to this embodiment, the carbon black and the oxide are dispersed throughout the entire surface treatment film. By dispersing the carbon black and the oxide throughout the surface treatment film, the emissivity of the surface treatment film at a wavelength of 8.0 μm at 25° C. can be made uniform throughout the entire film. As a result, when the portion to which the surface treatment film according to this embodiment is applied is hot stamped, the surface treatment film can be heated uniformly throughout.

[0035] The distribution state of the carbon black and the oxides can be confirmed by area analysis of the surface treatment film with an electron probe micro analyzer (EPMA) for elements derived from the carbon black (e.g., C) and elements derived from the oxides (i.e., Zr, Zn, Ti).

[0036] In addition, when a laminated film is formed by separately preparing a treatment liquid containing carbon black and a treatment liquid containing an oxide and separately applying these treatment liquids, the carbon black and the oxide do not exist in a dispersed state throughout the film. Furthermore, when attempting to form a film using a plurality of treatment liquids in this manner, a second layer of film must be formed after the first layer is formed, which increases the size of the production equipment and the production costs.

[0037] In addition, the surface treatment film according to this embodiment has a carbon black adhesion amount X CB and the amount of oxide adhesion X OxideBy satisfying the relationship represented by the above formula (1), the emissivity at 25°C at a wavelength of 8.0 μm becomes 60% or more, and the difference in the temperature rise rate with the part where the surface treatment film does not exist becomes significant. If the value specified in the middle term of the above formula (1) is less than 118.9, the amount of carbon black and oxide attached is insufficient, and the above-mentioned emissivity cannot be realized. The value specified in the middle term of the above formula (1) is preferably 119.0 or more, more preferably 170.0 or more, and even more preferably 220.0 or more. On the other hand, if the value specified in the middle term of the above formula (1) exceeds 332.0, the adhesion of the film decreases, which is not preferable. The value specified in the middle term of the above formula (1) is preferably 330.0 or less, more preferably 310.0 or less, and even more preferably 300.0 or less.

[0038] Here, the amount of carbon black attached to the surface treatment film is X CB can be measured by cross-sectional analysis of the surface treatment film using a transmission electron microscope (TEM) as follows. That is, a region represented by film thickness x 5 μm is cross-sectionally analyzed by TEM-EDS analysis to measure the film thickness of the surface treatment film and the area ratio occupied by particles with a carbon content of 70 mass % or more. When the film thickness is d (μm) and the area ratio is a (%), the value represented by d x a is the amount of carbon black attached X CB (g / m 2 )

[0039] In addition, the amount of oxide of at least one of Zr, Zn, and Ti in the surface treatment film is X Oxide means the amount of Zr oxide, Zn oxide, and Ti oxide (i.e., ZrO2, ZnO, and TiO2) adhering per unit area as metal Zr, metal Zn, and metal Ti. The amount of these oxides adhering, X Oxide can be determined by performing elemental analysis on the surface of the surface treatment film using an X-ray fluorescence analyzer (ZSX Primus, manufactured by RIGAKU Corporation) and quantifying the amounts of metallic Zr, metallic Zn, and metallic Ti.

[0040] The steel sheet for hot stamping according to this embodiment has the above-mentioned characteristics, and therefore can achieve an emissivity of 60% or more at a wavelength of 8.0 μm at 700° C. Below, the substances contained in the surface treatment film, which are characteristic for achieving the above-mentioned emissivity, will be described in more detail.

[0041] Carbon black The amount of carbon black attached to the surface treatment film in the area of ​​the surface of the steel sheet where the surface treatment film is applied is X CB is 0.030g / m 2 It is preferable that the amount of adhesion is equal to or more than X. CB 0.030g / m 2 By setting the temperature to 700° C. or more, it is possible to reliably increase the temperature rise rate in the range up to 700° C. CB is more preferably 0.100 g / m 2 On the other hand, the adhesion amount X CB The upper limit of the adhesion amount X is determined by the above formula (1). CB is preferably 0.800 g / m 2 More preferably, it is 0.600 g / m or less. 2 The following is the result.

[0042] Moreover, the surface treatment film more preferably contains 5.0 to 40.0% by volume of carbon black. Carbon black has the effect of increasing the temperature rise rate, particularly in the range up to 700°C. The thickness of the surface treatment film may vary locally due to the roughness or waviness of the steel sheet, or the difference in the rate at which volatile components such as water in the treatment solution evaporate during film formation. In this case, by having the carbon black content of 5.0% by volume or more, the difference between the part that appears black due to carbon black and the other parts can be suppressed, and the design can be maintained, which is preferable in terms of appearance. On the other hand, by having the carbon black content in the surface treatment film of 40.0% by volume or less, the decrease in paint adhesion after hot stamp heating can be suppressed. Although the mechanism is not clear, it is presumed that the inhibition of the binding between the paint and the substrate is suppressed by suppressing the remaining carbon black or compounds derived from the oxides of carbon black.

[0043] In addition, since the main components of carbon black are carbon, hydrogen, and oxygen, carbon black disappears when heated to high temperatures. Therefore, by including carbon black in the surface treatment film, it is possible to maintain performance after hot stamping, such as adhesion after painting.

[0044] By the carbon black content being 5.0% by volume or more, oxidation of the steel sheet or plating layer located under the surface treatment film is suppressed, so that reactivity is ensured when a paint (treatment agent) is applied, strong bonding is achieved, and paint adhesion is maintained. In addition, the emissivity can be increased, and the temperature rise rate can be increased. The carbon black content in the surface treatment film is more preferably 8.0% by volume or more. By making the carbon black content in the surface treatment film 8.0% by volume or more, it is possible to further increase the temperature rise rate. On the other hand, by making the carbon black content in the surface treatment film 40.0% by volume or less, it is possible to suppress an increase in the coating cost while sufficiently obtaining the effect of increasing the emissivity. The carbon black content in the surface treatment film is more preferably 30.0% by volume or less. By making the carbon black content in the surface treatment film 30.0% by volume or less, it is possible to further suppress the coating cost.

[0045] <Metal oxide> The total amount of Zr oxide, Zn oxide, and Ti oxide in the surface treatment film at the portion of the surface of the steel sheet where the surface treatment film is applied is X Oxide is 0.030g / m 2 It is preferable that the amount of adhesion is equal to or more than X. Oxide 0.03g / m 2 By setting the temperature to 700° C. or higher, it is possible to reliably increase the rate of temperature rise in the range of 700° C. or higher. Oxide is more preferably 0.060 g / m 2 On the other hand, the adhesion amount X Oxide The upper limit of the adhesion amount X is determined by the above formula (1). Oxide is preferably 0.500 g / m 2 More preferably, it is 0.300 g / m or less. 2 The following is the result.

[0046] Moreover, the surface treatment film more preferably contains Zr oxide, Zn oxide, and Ti oxide in a total amount of 1.0 to 30.0% by volume. The oxides of these elements (i.e., metal oxides of Zr, Zn, and Ti) remain in the surface treatment film even when heated to a high temperature of 700°C or higher at which the effect of carbon black is reduced. As a result, in the portion to which the surface treatment film is applied, these metal oxides have a higher emissivity than the steel sheet surface or the plated surface at a high temperature of 700°C or higher, so that the amount of heat input due to radiant heat from the heating atmosphere is increased. This makes it possible to maintain the effect of increasing the temperature rise rate even at a high temperature of 700°C or higher. By making the content of these metal oxides 1.0% by volume or more, the effect of increasing the temperature rise rate can be sufficiently obtained. The content of these metal oxides is more preferably 3.0% by volume or more. On the other hand, by making the content of these metal oxides 30% by volume or less, the film cost can be suppressed, which is economically preferable. The content of these metal oxides is more preferably 25.0% by volume or less.

[0047] The content (volume %) of various compounds such as carbon black and metal oxides in the surface treatment film can be calculated from the area percentage of the cross section by embedding the sample in resin, polishing it, and observing the cross section with a scanning electron microscope (SEM). The compounds can also be estimated by quantitative analysis using the EDX function attached to the SEM.

[0048] In the surface treatment film according to this embodiment, the adhesion amount X of the carbon black is CB (g / m 2 ) and the amount of oxide attached X Oxide (g / m 2 ) and the ratio X Oxide / X CB The ratio X is preferably 0.20 or more and 200.00 or less. Oxide / X CB By keeping the ratio X within the above range, it is possible to more appropriately heat the area to which the surface treatment film is applied. Oxide / X CBis more preferably 0.40 to 10.00, and further preferably 0.60 to 5.00.

[0049] Furthermore, the surface treatment film according to this embodiment may contain various binder components and additives in addition to the carbon black and metal oxides described above.

[0050] <Binder components> The binder component that can be contained in the surface treatment film according to this embodiment is preferably a water-dispersible or water-soluble resin. The content of the binder component selected from water-dispersible or water-soluble resins is preferably 40 volume % or more relative to the total volume of the surface treatment film.

[0051] As the binder component selected from water-dispersible or water-soluble resins, various known resins exhibiting water dispersibility or water solubility can be used. Examples of such resins exhibiting water dispersibility or water solubility include polyurethane resins, polyester resins, acrylic resins, epoxy resins, fluororesins, polyamide resins, polyolefin resins, and polymer compounds obtained by hydrolysis and condensation polymerization of silane coupling agents. It is more preferable that the binder component is one or more selected from the group consisting of polyester resins, polyurethane resins, polyolefin resins, acrylic resins, epoxy resins, fluororesins, and polyamide resins. In addition, when multiple resins are used as the binder component, the total content of the multiple resins used is treated as the content of the binder component.

[0052] In addition, when a polyurethane resin is used as the binder component, the polyurethane resin is preferably a polyether-based polyurethane resin, because the use of a polyether-based polyurethane resin can prevent the occurrence of hydrolysis caused by acid or alkali, compared with a polyester-based polyurethane resin, and because the use of a polyether-based polyurethane resin can suppress the formation of a hard and brittle film, compared with a polycarbonate-based polyurethane resin, thereby ensuring adhesion during processing and corrosion resistance of the processed part.

[0053] Whether or not polyurethane resin is contained can be determined by detecting the 3330 cm -1 (NH telescopic), 1730cm -1 (C=O expansion and contraction), 1530cm -1 (CN), 1250cm -1 It can be judged based on whether the characteristic absorption of (CO) is observed. In addition, the polyurethane resin content can also be determined from the obtained characteristic absorption intensity by creating a calibration curve showing the relationship between the content and the characteristic absorption intensity using a sample with a known content.

[0054] In addition, for resins other than the above polyurethane resins, it is possible to determine the presence or absence and the amount of content in the same manner as for the above polyurethane resins, by paying attention to the characteristic absorption derived from the functional groups specific to each resin.

[0055] Additives In the surface treatment film according to this embodiment, various additives such as a leveling agent, a water-soluble solvent, a metal stabilizer, an etching inhibitor, etc. can be contained as additives used in preparing the treatment liquid prior to film formation, within a range that does not impair the effects of the present invention.

[0056] The leveling agent may be a nonionic or cationic surfactant, such as a polyethylene oxide or polypropylene oxide adduct, or an acetylene glycol compound.

[0057] Examples of the water-soluble solvent include alcohols such as ethanol, isopropyl alcohol, t-butyl alcohol, and propylene glycol; cellosolves such as ethylene glycol monobutyl ether and ethylene glycol monoethyl ether; esters such as ethyl acetate and butyl acetate; and ketones such as acetone, methyl ethyl ketone, and methyl isobutyl ketone.

[0058] Examples of metal stabilizers include chelating compounds such as EDTA (ethylenediaminetetraacetic acid) and DTPA (diethylenetriaminepentaacetic acid).

[0059] Etch inhibitors include, for example, amine compounds such as ethylenediamine, triethylenepentamine, guanidine, and pyrimidine.

[0060] The contents of the binder components and additives can be measured in the same manner as in the case of carbon black and metal oxides.

[0061] <Silica> As mentioned above, the surface treatment film according to this embodiment may not contain silica, or may contain silica within a certain range. More specifically, the silica content in the surface treatment film according to this embodiment is 0 to 0.3 g / m 2 Silica is 0.3g / m 2 If the content exceeds 0.3 g / m, the temperature increase effect cannot be expected and the cost becomes high, which is not economically preferable. In addition, since silica is a substance with low electrical conductivity, the content of silica is less than 0.3 g / m 2 If the content exceeds 100%, it is not preferable in terms of weldability after hot stamping. When silica is contained, the smaller the silica content of the surface treatment film, the better. The silica content of the surface treatment film is more preferably 0.10 g / m 2 More preferably, it is 0.05 g / m or less. 2 The following is the result.

[0062] <Thickness of surface treatment film> The thickness of the surface treatment film containing the above components is preferably, for example, 0.5 to 5.0 μm. By setting the thickness of the surface treatment film within the above range, the emissivity at a wavelength of 8.0 μm at 25° C. can be more reliably set to 60% or more. The thickness of the surface treatment film is more preferably 1.0 to 3.0 μm.

[0063] <Metal plating layer> The hot stamping steel sheet according to the present embodiment preferably has a metal plating layer at least partially between the base steel sheet and the surface treatment film on one or both sides of the hot stamping steel sheet. By having the metal plating layer, the corrosion resistance after painting after hot stamping can be further improved. In addition, the presence of the metal plating layer can prevent iron scale from being generated by heating during hot stamping. Iron scale contaminates the heating furnace and adheres to rolls used for transportation, which is a burden in manufacturing. Therefore, when iron scale is generated, a process such as shot blasting is required to remove the iron scale, which is not economically preferable.

[0064] The type of the metal plating layer is not particularly limited. Examples of metal plating constituting the metal plating layer include aluminum plating, Al-Si plating, zinc plating, alloyed zinc plating, Zn-Ni plating, Zn-Al-Mg plating, and Zn-Al-Mg-Si plating.

[0065] The method for forming the metal plating layer includes, but is not limited to, hot-dip plating, electroplating, physical vapor deposition, chemical vapor deposition, and the like.

[0066] <Base material steel plate> Next, the base steel sheet of the hot stamping steel sheet according to the present embodiment is not particularly limited as long as it is a steel sheet suitable for use in the hot stamping process. As a steel sheet applicable to the hot stamping steel sheet according to the present embodiment, for example, a steel sheet containing, in mass%, C: 0.10 to 0.40%, Si: 0.01 to 0.60%, Mn: 0.50 to 3.00%, P: 0.05% or less, S: 0.020% or less, Al: 0.10% or less, Ti: 0.01 to 0.10%, B: 0.0001 to 0.0100%, N: 0.010% or less, with the balance being Fe and impurities, can be exemplified. In addition, as the form of the base steel sheet, for example, a steel sheet such as a hot rolled steel sheet or a cold rolled steel sheet can be exemplified. Hereinafter, the chemical components of the base steel sheet will be described in detail. In the following description of the chemical components of the base steel plate, the notation "%" means "mass %" unless otherwise specified.

[0067] [C:0.10~0.40%] C is contained to ensure the desired mechanical strength. When the C content is 0.10% or more, a sufficient improvement in mechanical strength is obtained, and the effect of containing C is fully obtained. Therefore, the C content is preferably 0.10% or more. The C content is more preferably 0.20% or more. On the other hand, when the C content is 0.40% or less, the strength of the steel sheet can be hardened and improved while the decrease in elongation and reduction of area can be suppressed. Therefore, the C content is preferably 0.40% or less. The C content is more preferably 0.35% or less.

[0068] [Si: 0.01~0.60%] Si is one of the strength-improving elements that improve mechanical strength, and is contained in order to secure the desired mechanical strength, similar to C. When the Si content is 0.01% or more, the strength-improving effect is fully exerted, and sufficient improvement in mechanical strength is obtained. Therefore, the Si content is preferably 0.01% or more. The Si content is more preferably 0.10% or more. On the other hand, since Si is also an easily oxidizable element, when the Si content is 0.60% or less, the decrease in wettability during hot-dip Al plating due to the influence of Si oxide formed on the steel sheet surface layer is suppressed, and the occurrence of bare spots can be suppressed. Therefore, the Si content is preferably 0.60% or less. The Si content is more preferably 0.40% or less.

[0069] [Mn: 0.50~3.00%] Mn is one of the strengthening elements that strengthen steel, and is also one of the elements that enhance hardenability. Furthermore, Mn is an element that is effective in preventing hot embrittlement caused by S, which is one of the impurities. When the Mn content is 0.50% or more, these effects can be sufficiently obtained. Therefore, in order to reliably exhibit the above effects, the Mn content is preferably 0.50% or more. The Mn content is more preferably 0.80% or more. On the other hand, since Mn is an austenite forming element, when the Mn content is 3.00% or less, the amount of retained austenite phase does not become too large, and a decrease in strength is suppressed. Therefore, the Mn content is preferably 3.00% or less. The Mn content is more preferably 1.50% or less.

[0070] [P:0.05% or less] P is an impurity contained in steel. By making the P content 0.05% or less, it is possible to suppress the P contained in the steel sheet from segregating at the grain boundaries of the steel sheet and reducing the toughness of the base material of the hot stamped body, and to suppress the reduction in the delayed fracture resistance of the steel sheet. Therefore, the P content is preferably 0.05% or less, and it is preferable to make the P content as small as possible.

[0071] [S:0.020% or less] S is an impurity contained in steel. By making the S content 0.020% or less, it is possible to suppress the S contained in the steel sheet from forming sulfides that reduce the toughness of the steel sheet, and to suppress a decrease in the delayed fracture resistance of the steel sheet. Therefore, the S content is preferably 0.020% or less, and it is preferable to make the S content as small as possible.

[0072] [Al: 0.10% or less] Al is generally used for the purpose of deoxidizing steel. On the other hand, by making the Al content 0.10% or less, the increase in Ac3 point of the steel sheet is suppressed, so that the heating temperature required to ensure the hardenability of the steel during hot stamping can be reduced, which is desirable for hot stamping production. Therefore, the Al content of the steel sheet is preferably 0.10% or less, more preferably 0.05% or less, and further preferably 0.01% or less.

[0073] [Ti: 0.01~0.10%] Ti is one of the strength enhancing elements. When the Ti content is 0.01% or more, the strength improving effect and the oxidation resistance improving effect can be sufficiently obtained. Therefore, in order to reliably realize the above effects, the Ti content is preferably 0.01% or more. The Ti content is more preferably 0.03% or more. On the other hand, when the Ti content is 0.10% or less, for example, the formation of carbides and nitrides is suppressed, the softening of the steel can be suppressed, and the desired mechanical strength can be sufficiently obtained. Therefore, the Ti content is preferably 0.10% or less. The Ti content is more preferably 0.08% or less.

[0074] [B:0.0001~0.0100%] B acts during quenching to improve strength. When the B content is 0.0001% or less, such a strength improving effect can be sufficiently obtained. Therefore, the B content is preferably 0.0001% or more. The B content is more preferably 0.0010% or more. On the other hand, when the B content is 0.0100% or less, the formation of inclusions is reduced, embrittlement of the steel sheet is suppressed, and a decrease in fatigue strength can be suppressed. Therefore, the B content is preferably 0.0100% or less. The B content is more preferably 0.0040% or less.

[0075] [N:0.010% or less] N is an impurity contained in steel. By making the N content 0.010% or less, the formation of nitrides due to N contained in the steel plate is suppressed, and the deterioration of the toughness of the steel plate can be suppressed. Furthermore, when B is contained in the steel plate, the N contained in the steel plate is suppressed from combining with B to reduce the amount of solid-solubilized B, and the deterioration of the hardenability improving effect of B can be suppressed. Therefore, the N content is preferably 0.010% or less, and it is more preferable to make the N content as small as possible.

[0076] In addition, the base steel sheet of the hot stamping steel sheet according to this embodiment may further contain elements such as Cr, Mo, Ni, Co, Cu, Mo, V, Nb, Sn, W, Ca, REM, O, and Sb as optional added elements.

[0077] [Cr:0~1.00%] Cr is an element that improves the hardenability of steel sheet. In order to fully obtain this effect, the Cr content is preferably 0.01% or more. On the other hand, by making the Cr content 1.00% or less, the effect can be fully obtained while suppressing an increase in costs. Therefore, when Cr is contained, the Cr content is preferably 1.00% or less.

[0078] [Ni:0~2.00%] [Co: 0-2.00%] Ni and Co are elements that improve the hardenability of steel and enable the strength of the steel plate member after hardening to be stably ensured. In order to fully exert such effects, the Ni content is preferably 0.10% or more, and the Co content is preferably 0.10% or more. On the other hand, by making the Ni content and the Co content each 2.00% or less, the above effects can be fully obtained while improving economic efficiency. Therefore, when contained, the Ni content is preferably 2.00% or less, and the Co content is preferably 2.00% or less.

[0079] [Cu:0~1.000%] Cu is an element that enhances the hardenability of steel and enables the strength of the steel plate member after hardening to be stably secured. Cu also improves pitting corrosion resistance in a corrosive environment. In order to fully exert such effects, it is preferable that the Cu content is 0.100% or more. On the other hand, by making the Cu content 1.000% or less, the above effects can be sufficiently obtained while improving economic efficiency. Therefore, when Cu is contained, it is preferable that the Cu content is 1.000% or less.

[0080] [Mo:0~1.00%] Mo is an element that enhances the hardenability of steel and enables the strength of the steel plate member after hardening to be stably ensured. In order to fully exert such effects, the Mo content is preferably 0.10% or more. On the other hand, by making the Mo content 1.00% or less, the above effects can be sufficiently obtained while improving economic efficiency. Therefore, when Mo is contained, the Mo content is preferably 1.00% or less.

[0081] [V:0~1.00%] V is an element that enhances the hardenability of steel and enables the strength of the steel plate member after hardening to be stably ensured. In order to fully exert such effects, it is preferable that the V content is 0.10% or more. On the other hand, by making the V content 1.00% or less, the above effects can be sufficiently obtained while improving economic efficiency. Therefore, when V is contained, it is preferable that the V content is 1.00% or less.

[0082] [Nb: 0-1.00%] Nb is an element that enhances the hardenability of steel and enables the strength of the steel plate member after hardening to be stably ensured. In order to fully exert such effects, the Nb content is preferably 0.01% or more. On the other hand, by making the Nb content 1.00% or less, the above effects can be sufficiently obtained while improving the economic efficiency. Therefore, when Nb is contained, the Nb content is preferably 1.00% or less.

[0083] [Sn: 0~1.00%] Sn is an element that improves pitting corrosion resistance in a corrosive environment. In order to fully exert this effect, the Sn content is preferably 0.01% or more. On the other hand, by making the Sn content 1.00% or less, the decrease in grain boundary strength is suppressed, and the decrease in toughness can be suppressed. Therefore, when Sn is contained, the Sn content is preferably 1.00% or less.

[0084] [W:0~1.00%] W is an element that enhances the hardenability of steel and enables the strength of the steel plate member after hardening to be stably secured. W also improves pitting corrosion resistance in a corrosive environment. In order to fully exert such effects, it is preferable that the W content is 0.01% or more. On the other hand, by making the W content 1.00% or less, the above effects can be sufficiently obtained while improving economic efficiency. Therefore, when W is contained, it is preferable that the W content is 1.00% or less.

[0085] [Ca: 0~0.010%] Ca is an element that has the effect of refining inclusions in steel and improving toughness and ductility after quenching. In order to fully exert such effects, the Ca content is preferably 0.001% or more, and more preferably 0.002% or more. On the other hand, by making the Ca content 0.010% or less, the effect can be sufficiently obtained while the cost can be suppressed. Therefore, when Ca is contained, the Ca content is preferably 0.010% or less, and more preferably 0.004% or less.

[0086] [REM:0~0.30%] Like Ca, REM is an element that has the effect of refining inclusions in steel and improving toughness and ductility after quenching. In order to fully exert such effects, the REM content is preferably 0.001% or more, and more preferably 0.002% or more. On the other hand, by making the REM content 0.30% or less, the effect can be sufficiently obtained while suppressing costs. Therefore, when REM is contained, the REM content is preferably 0.30% or less, and more preferably 0.20% or less.

[0087] Here, REM refers to Sc, Y and lanthanoids, a total of 17 elements, and the above REM content means the total content of these elements. REM is added to molten steel using, for example, an Fe-Si-REM alloy, which includes, for example, Ce, La, Nd, and Pr.

[0088] [O:0.0070% or less] O is not an essential element, and is contained in steel as an impurity, for example. O is an element that causes deterioration of the properties of steel sheets by forming oxides and becoming the starting point of fracture. In addition, oxides present in the vicinity of the surface of the steel sheet may cause surface defects and deteriorate the appearance quality. For this reason, the lower the O content, the better. In particular, by making the O content 0.0070% or less, deterioration of properties can be suppressed, so the O content is preferably 0.0070% or less. The lower limit of the O content is not particularly limited and may be 0%, but the practical lower limit of the O content in actual operation and refining is 0.0005%.

[0089] [Sb:0.100% or less] The lower limit of the Sb content is not particularly limited, and may be 0%. Sb is an effective element for improving the wettability and adhesion of plating. To obtain this effect, it is preferable to contain 0.001% or more of Sb. On the other hand, by keeping the Sb content at 0.100% or less, it is possible to suppress defects that occur during manufacturing and to suppress a decrease in toughness. Therefore, the Sb content is preferably 0.100% or less.

[0090] The balance other than the above components is Fe and impurities. The base steel sheet may also contain impurities that are mixed in during the manufacturing process, etc. Examples of such impurities include Zn (zinc).

[0091] An example of the chemical components of the base steel sheet of the hot stamping steel sheet according to this embodiment has been described in detail above.

[0092] The area of ​​the steel sheet having the above chemical composition and surface treatment film applied thereto can be made into a hot stamped component having a tensile strength of about 1000 MPa or more by heating and quenching using a hot stamping method. In addition, in the hot stamping method, press working can be performed in a softened state at high temperature, so that the material can be easily formed.

[0093] The hot stamping steel sheet according to the present embodiment does not require the use of multiple steel sheets and does not require equipment and processes for welding in advance, as compared with the case where different steel sheets are welded together and then hot stamped, or the method of changing the cooling rate depending on the location by controlling the temperature of the die. In addition, no equipment for changing the temperature of the die and the running costs thereof are required. Therefore, it is economically preferable.

[0094] <Manufacturing of hot stamped components having parts with different strengths> In the case of automobile frame parts, some parts may have high strength and other parts may have low strength in order to absorb energy during a collision. Such parts having different strengths can be manufactured using a hot stamping steel sheet having a region in which a surface treatment film is applied to a part of the surface, as described above.

[0095] First, a surface treatment film is applied to a part of the surface of a metal material such as a coiled steel sheet, and portions with different emissivity are formed in advance. Then, various processes such as cutting and punching with a press are performed to obtain the hot stamping steel sheet according to this embodiment. Alternatively, the hot stamping steel sheet according to this embodiment can be obtained by applying a surface treatment film to a steel sheet that has been cut or punched with a press. Furthermore, the emissivity can be continuously changed by changing the film thickness of the surface treatment film.

[0096] For example, the hot stamping steel sheet to which the surface treatment film is applied as described above is hot stamped. Examples of the heating device include an electric heating furnace, a gas heating furnace, a far-infrared furnace, and a normal heating device equipped with an infrared heater. As shown in FIG. 1, the portion to which the surface treatment film is applied (coated portion) has a high emissivity and a large heat transfer effect by radiation, so the temperature rise rate is fast, but the temperature rise rate of other portions (non-coated portions) is slow. The coated portion, which is heated quickly and has a high temperature, is heated to a temperature of Ac3 point or higher at which the metal structure transforms into the austenite phase. On the other hand, the non-coated portion has a slow temperature rise rate, so that even if the coated portion reaches a temperature of Ac3 point or higher, the temperature can be kept below Ac3 point at which the metal structure does not completely transform into the austenite single phase. In this embodiment, the heating device to be used may be appropriately controlled so that the above-mentioned state is realized.

[0097] Next, the heated steel plate is formed and cooled. The portion heated to the Ac3 point or higher, at which the metal structure of the steel material transforms into the austenite phase, is quenched and has high strength, while the portion heated to a temperature below the Ac3 point and not yet transformed into the austenite single phase has relatively low strength. As a result, a part having portions with different strengths (i.e., hot stamped member) can be obtained, and further, the difference in strength between the portions with different strengths can be made 150Hv or more in Vickers hardness (load F: 50kgf, 1kgf is approximately 9.8N) as defined in JIS Z 2244 (2009).

[0098] As described above, by changing the thickness of the surface treatment film, the rate of temperature rise also changes continuously, and by utilizing this, the hardness can also be changed continuously. In the area where the surface treatment film is thick, the rate of temperature rise is high, so austenitization progresses the most, and the strength increases due to the formation of martensite during quenching during cooling. On the other hand, in the area where the film is thin, the austenite phase ratio during heating is low, and the amount of martensite formed is less than in the area where the film is thick, so the strength is lower. In addition, in the area where no film is applied, the austenite phase ratio during heating is even lower, and the amount of martensite formed is even less, so the strength is even lower.

[0099] In this way, in the steel sheet for hot stamping according to the present embodiment, by appropriately controlling the parts to which the surface treatment film is applied and the film thickness, when the steel sheet for hot stamping is used to manufacture a hot stamped component, parts having different strengths can be produced as desired.

[0100] <Hot stamping parts> The hot stamped member obtained in the above manner has a portion having a surface treatment film and a portion not having the surface treatment film on the surface of the steel sheet. The surface treatment film contains one or more oxides selected from the group consisting of Zr oxide, Zn oxide, and Ti oxide, and has an oxide adhesion amount X Oxide is 0.030g / m 2 The surface treatment film has a silica content of 0 to 0.3 g / m 2 The carbon black present in the surface treatment film of the hot stamping steel sheet used as the material for the hot stamping component disappears through the hot stamping process, and the above metal oxides remain. The amount of oxide adhesion X present in the surface treatment film of the hot stamping component Oxide depends on the amount of oxide in the surface treatment film of the hot stamping steel sheet used as the base material, but the upper limit is approximately 0.600 g / m 2 It is.

[0101] When the Vickers hardness of such a hot stamped member is measured according to JIS Z 2244 (2009) (load F: 50 kgf, 1 kgf is approximately 9.8 N), it is preferable that the hot stamped member has a portion exhibiting a maximum hardness HVmax and a portion exhibiting a minimum hardness HVmin, and that the hardness difference ΔHV between the maximum hardness HVmax and the minimum hardness HVmin is 150 or more.

[0102] As is clear from the above description, both the portion showing the maximum hardness HVmax and the portion showing the minimum hardness HVmin are present in a region made of a common material (i.e., the hot stamping steel sheet according to the present embodiment). Here, the "common member" refers to a case where the ratio (ratio between members) of the content of a specific element (e.g., C, Si, Mn, P, S, Al, Ti, B, N) in a 0.05 mm field near the center of the sheet thickness is anywhere within a range of 0.80 to 1.2 times. For example, a member that has the same composition when confirmed at the center of the sheet thickness and is manufactured through the same manufacturing process is the "common member" referred to here. Note that such a common material may be made of one steel sheet, or may be made of a plurality of identical steel sheets (i.e., the hot stamping steel sheet according to the present embodiment) joined together by some method. EXAMPLES

[0103] Examples of the present invention will be described below, but the conditions in the examples are merely examples of conditions adopted to confirm the feasibility and effects of the present invention, and the present invention is not limited to these examples. Various conditions may be adopted in the present invention as long as they do not deviate from the gist of the present invention and achieve the object of the present invention.

[0104] It is preferable to use a steel sheet having high mechanical strength (meaning various properties related to mechanical deformation and destruction such as tensile strength, yield point, elongation, reduction in area, hardness, impact value, fatigue strength, etc.) as the base steel sheet. The chemical composition of the base steel sheet before plating used in the hot stamping steel sheets shown in the following examples is shown in Table 1 below.

[0105] [Table 1]

[0106] A surface treatment film was applied to base steel plate (steel Nos. S1 to S18) having the chemical composition shown in Table 1. More specifically, as shown in Fig. 2, in a steel plate having a width of 100 mm, a length of 200 mm and a thickness of 1.2 mm, a surface treatment film was applied to one or both sides of the upper half 100 mm of the 200 mm in the longitudinal direction to form a coated region, and the remaining 100 mm was not applied with a surface treatment film and was formed as an uncoated region.

[0107] In addition to the water-based acrylic resin, which is a binder component, a water-based treatment liquid containing at least one of commercially available carbon black and compounds such as TiO2, ZrO2, ZnO, Fe2O3, Fe3O4, CuO, SiO2, TiC, TiN, SiC, and SiN was applied to a part of the base steel sheet using an industrial inkjet printer and dried to provide a surface treatment film. In addition to the above components, some of the water-based treatment liquids further contained silica. The thickness of the surface treatment film was within the range of 1.0 to 2.5 μm, and when applied to both sides, the same type of film was applied to both sides.

[0108] Then, a thermocouple was connected to the center (P1) of the portion to which the surface treatment film was applied (coated portion) and the center (P2) of the portion without the coating (non-coated portion) shown in FIG. 2, respectively, so that the temperature at each position could be measured. Then, the steel sheet was heated in an electric heating furnace set at a temperature of 900°C, and when the portion to which the film was applied reached 880°C, the steel sheet was removed from the heating furnace. The steel sheet was rapidly cooled with a flat die to obtain a hot stamped component. Note that, when the Vickers hardness of the manufactured hot stamped component was measured, the portion to which the surface treatment film was applied (coated portion) was the portion that exhibited the maximum hardness HVmax, and the portion to which the surface treatment film was not applied (non-coated portion) was the portion that exhibited the minimum hardness HVmin when the Vickers hardness of the manufactured hot stamped component was measured.

[0109] Using a radiation thermometer, the radiation intensity at the center P1 of the portion to which the surface treatment film was applied was measured at 25° C. with a wavelength of 8.0 μm, and the emissivity (%) was calculated from the ratio to the radiation intensity of a black body.

[0110] Some of the base steel sheets were plated with Al-10% Si by mass, Zn by mass, or Al by hot-dip galvanization, and then the above-mentioned surface treatment film was applied, or the base steel sheets were plated with Zn-3% Ni by mass by electroplating, and then the above-mentioned surface treatment film was applied. In the case of the hot-dip galvanization method, the base steel sheets were immersed in a plating bath, and then the coating weight was reduced to 70 g / m per side by gas wiping. 2 In the case of electroplating, the coating weight on one side was adjusted to 20 g / m 2 was adjusted to.

[0111] The coating composition of the area where the surface treatment coating was applied and the difference in Vickers hardness between P1 and P2 of the obtained hot stamped parts were investigated. In some examples, the appearance, paint adhesion, and corrosion resistance after painting were also investigated. The evaluation methods for each evaluation item were as follows.

[0112] (1) Strength characteristics (Score) Using the method described in the Japanese Industrial Standard JIS Z 2244 (2009), the Vickers hardness was measured from the cross section of the steel plate at the center P1 of the area where the surface treatment film was applied and the center P2 of the area where the surface treatment film was not applied (load F: 50 kgf). The strength characteristics were evaluated based on the hardness difference between P1 and P2, and if the hardness difference was Hv150 or more, the component was determined to have excellent strength characteristics with different strengths. 3: Vickers hardness difference ΔHV is Hv200 or more 2: Vickers hardness difference ΔHV is Hv150 or more but less than 200 1: Vickers hardness difference ΔHV is less than Hv150

[0113] (2) Appearance (Score) The CIE 1976 L*a*b* color space was measured at five locations using the method described in the Japanese Industrial Standard JIS Z 8781-4 (2013), and the ratio of the L* value (RL*=L*value1 / L*value2) was evaluated when comparing any two locations. 2:0.5~2.0 1: Less than 0.5 or more than 2.0

[0114] (3) Paint adhesion The sample was subjected to a phosphating conversion treatment and a 15 μm thick electrodeposition coating, and then baked at 170°C for 20 minutes to provide a coating. After that, it was immersed in deionized water at 60°C for 200 hours, after which 100 grids spaced 1 mm apart were cut with a cutter, and the number of peeled areas of the grids was visually counted to calculate the area ratio of the peeled areas. The sample was scored based on the calculated area ratio. (Score) 3: Peeling area 0% to less than 10% 2: Peeling area is 10% or more but less than 70% 1: Peeling area 70% to 100%

[0115] (4) Corrosion resistance after painting A scratch was made in the coating film applied in the same manner as in (3) with a cutter, and the method was performed according to JASO M609 established by the Society of Automotive Engineers of Japan. The width of the coating blister from the scratch (maximum value on one side) after 180 cycles of the corrosion test was measured. (Score) 3: Bulge width 0mm to less than 1.5mm 2: Bulge width 1.5mm or more but less than 3mm 1: Bulge width 3mm or more

[0116] The evaluation results obtained in Examples 1 to 4 carried out under the above conditions are shown in Tables 2, 3, 4 and 5, respectively.

[0117] <Example 1> In Table 2 below, A1~ 17 is an embodiment, A18 to A21 are reference examples. a1 to a3 are comparative examples. In this Example 1, when preparing the aqueous treatment liquid, at least one of carbon black, titanium nitride, titanium carbide, titanium oxide, iron oxide, copper oxide, zirconium oxide, silicon nitride, cobalt oxide, and tin oxide was used as a compound other than the binder component. The total content of the compounds other than the binder component in the aqueous treatment liquid was set to be within the range of 2 to 50 volume % with respect to the total volume of the solid content. The aqueous treatment liquid was set to have a solid content concentration of 10 to 40 mass %, and was applied to a steel plate so as to have a liquid film thickness of 3 μm to 25 μm, and then dried to obtain a film. The atmosphere during drying was air or nitrogen atmosphere, and the temperature was 100 to 300° C. The total content of the compounds in the aqueous treatment liquid is the total content of the compounds in the surface treatment film obtained after drying. In this Example, the emissivity value at a wavelength of 8.0 μm was adjusted by adjusting the content of the compounds and the adhesion amount of the surface treatment film.

[0118] [Table 2]

[0119] In Comparative Examples a1 to a3, the emissivity of the coated portion P1 at 25°C and a wavelength of 8.0 μm was small, at 58, 56, and 58%, and the hardness difference between the coated portion P1 and the uncoated portion P2 of the hot stamped component was less than ΔHV150 in Vickers hardness (rating 1). Since the coatings of a1 to a3 have emissivity of less than 60% at a wavelength of 8.0 μm at 25°C, there is no significant difference in the rate of temperature rise during heating between the coated portion P1 and the uncoated portion P2, and it is presumed that there was no difference in Vickers hardness of ΔHV150 or more in the structure of the hot stamped component.

[0120] On the other hand, invention examples A1~ 17 and Reference Example A18~ For A21, the emissivity was 60% or more at 25°C and a wavelength of 8.0 μm. As a result, the difference in hardness between the coated and uncoated areas of the hot stamped component was HV150 or more and less than 200 (rating 2) in Vickers hardness.

[0121] <Example 2> In Table 3, in Example B1, the carbon black (CB) was 2.7% by volume in the surface treatment film, and the TiO2 was 0.6% by volume in the surface treatment film. As a result, the emissivity at 25°C and a wavelength of 8.0 μm in the coated area was 86%, and the hardness difference between the coated area and the uncoated area of ​​the hot stamped component was a Vickers hardness of HV 150 or more and less than 200 (score 2). The paint adhesion was scored 3, but the appearance was scored 1. In Example B2, in which the carbon black was 4.0% by volume in the surface treatment film and the TiO2 was 1.0% by volume in the surface treatment film, the emissivity at 25°C and a wavelength of 8.0 μm in the coated area was 80%, and the hardness difference between the coated area and the uncoated area of ​​the hot stamped component was a Vickers hardness of HV 150 or more and less than 200 (score 2). The carbon black content in the surface treatment film was 58.3% by volume, and the ZnO content in the surface treatment film was 1.2% by volume. Reference example B5, carbon black was 47.3% by volume in the surface treatment film, and ZnO was 1.0% by volume in the surface treatment film. Reference example For B6, the emissivity at 25°C and a wavelength of 8.0 μm in the coated area was 88% and 90%, respectively, and the appearance was given a score of 2. In addition, the paint adhesion was also given a score of 2.

[0122] On the other hand, in Examples B3 and B4, in which the carbon black content in the surface treatment coating was 5.0% by volume to 40.0% by volume, the emissivity of the coated areas at 25°C and a wavelength of 8.0 μm was 82% and 86%, and the hardness difference between the coated and uncoated areas of the hot stamped component was a Vickers hardness of HV200 or more (score 3), and the appearance was scored 2 and the paint adhesion was scored 3.

[0123] From the above results, it was found that by containing 5.0 volume % to 40.0 volume % of carbon black, as in invention examples B3 to B4, molded articles excellent not only in strength characteristics but also in appearance and paint adhesion were obtained.

[0124] [Table 3]

[0125] <Example 3> In Table 4, the Zn oxide content in the surface treatment film was set to 0.2% by volume. Reference example Compared with C1, invention example C2 in which the Ti oxide content in the surface treatment film was 0.3 volume %, and invention example C6 in which the Ti oxide content in the surface treatment film was 37.5 volume %, invention examples C3 to C5 in which the Ti oxide and Zr oxide contents in the surface treatment film were 1.0 to 30.0 volume % further increased the difference in hardness between the coated and uncoated areas of the hot stamped component (score 3). The reason for the increased hardness difference is believed to be that the emissivity of the oxide is higher than that of the compounds on the steel sheet surface, and that the presence of the interface between the steel sheet surface and oxide particles prevents infrared light reflection, increasing the amount of heat input to the sample, thereby increasing the difference in heating rate with the uncoated area.

[0126] [Table 4]

[0127] <Example 4> In Table 5, in Example D1, the emissivity of the coated area at 700°C and a wavelength of 8.0 μm was 56%, and the hardness difference between the coated area and the uncoated area of ​​the hot stamped part was a Vickers hardness of HV150 or more and less than 200 (score 2). On the other hand, in Example D2, the emissivity of the coated area at 700°C and a wavelength of 8.0 μm was 60% or more. , D3, and Reference Example D4 In the case of D6, the difference in hardness between the coated and uncoated areas of the hot stamped parts was a Vickers hardness of HV200 or more (rating 3).

[0128] [Table 5]

[0129] <Example 5> In Table 6, Reference example E1 and Example E2 ~E5 and 、As is clear from the comparison of the uncoated invention example E6 with the uncoated invention example E6, the corrosion resistance after painting was rated "1", whereas the uncoated invention example E6 with the coating of Al-10% Si or Zn-3% Ni was rated "1". Reference example E1 and Example E2 After painting, corrosion resistance of E5 was improved to "2" or "3".

[0130] [Table 6]

[0131] As described above, according to the present invention, by applying a surface treatment film to desired portions of a steel plate and then hot stamping, it is possible to form portions having different strengths in the obtained hot stamped member.

[0132] Although the preferred embodiment of the present invention has been described in detail above with reference to the accompanying drawings, the present invention is not limited to such an example. It is clear that a person having ordinary knowledge in the technical field to which the present invention pertains can conceive of various modified or altered examples within the scope of the technical ideas described in the claims, and it is understood that these also naturally belong to the technical scope of the present invention. [Industrial Applicability]

[0133] According to the present invention, in an area to which a surface treatment film having an increased emissivity at a wavelength of 8.0 μm at 25° C. is applied, heat transfer by radiation is increased, making it possible to heat the material rapidly. By providing a difference in hardenability, it is possible to provide areas with different strengths in a hot stamped part from a single steel sheet. Therefore, the present invention has a high industrial applicability.

Claims

1. The steel sheet has a surface including a portion having a surface treatment film having an emissivity of 60% or more at a wavelength of 8.0 μm at 25° C. and a portion not having the surface treatment film, the surface treatment film contains carbon black and one or more oxides selected from the group consisting of Zr oxide and Ti oxide, the carbon black and the oxides being present in a dispersed state throughout the surface treatment film, The surface treatment film has a silica content of 0 to 0.3 g / m 2 and The amount of the carbon black and the amount of the oxide attached are each X CB (g / m 2 ), X Oxide (g / m 2 ) a steel sheet for hot stamping, which satisfies the following formula (1): 118.9≦24280 / {6700 / (100+76×X CB )+18000 / (130+65×X Oxide )}≦332.0 ………… Formula (1)

2. The steel sheet for hot stamping according to claim 1, wherein the surface treatment film contains 5.0 to 40.0 vol. % of the carbon black and 1.0 to 30.0 vol. % of the oxide.

3. The amount of carbon black attached X CB (g / m 2 ) and the amount of oxide attached X Oxide (g / m 2 ) and the ratio X Oxide / X CB The steel sheet for hot stamping according to claim 1 or 2, wherein is 0.20 or more and 200.00 or less.

4. The amount of carbon black attached X CB is 0.030 g / m 2 or more, and the amount of adhesion of the oxide X Oxide is 0.030 g / m 2 The steel sheet for hot stamping according to any one of claims 1 to 3.

5. The steel sheet for hot stamping according to any one of claims 1 to 4, wherein the surface treatment coating has an emissivity at 700 ° C. at a wavelength of 8.0 μm of 60% or more.

6. The steel sheet for hot stamping according to any one of claims 1 to 5, wherein a metal plating layer is provided between a substrate of the steel sheet and the surface treatment film on one or both sides of the steel sheet for hot stamping.

7. The steel sheet has a surface having a portion having a surface treatment film and a portion not having the surface treatment film, The surface treatment film contains one or more oxides selected from the group consisting of Zr oxide and Ti oxide, and the amount of adhesion of the oxide is X Oxide is 0.030 g / m 2 That's all. The surface treatment film has a silica content of 0 to 0.3 g / m 2 A hot stamped component.

8. 8. The hot stamped member according to claim 7, wherein, when a Vickers hardness defined in JIS Z 2244 (2009) is measured, a portion exhibiting a maximum hardness HVmax and a portion exhibiting a minimum hardness HVmin are present, and a hardness difference ΔHV between the maximum hardness HVmax and the minimum hardness HVmin is 150 or more.

9. 9. The hot stamped member according to claim 8, wherein both the portion exhibiting the maximum hardness HVmax and the portion exhibiting the minimum hardness HVmin are present in a region made of a common material.

Citation Information

Patent Citations

  • Al PLATED STEEL SHEET FOR HOT PRESS HAVING EXCELLENT TEMPERATURE RISING PROPERTY, AND METHOD FOR PRODUCING THE SAME

    JP2011149084A

  • Steel sheet for radiation heating, which is suitable to produce metallic processed article having portion with different strength and which is used for hot stamping and method of producing the same

    JP2011152589A

  • Hot press molding and manufacturing method thereof

    JP2014161854A

  • Press molded article and hot press molding method

    JP2016041440A

  • Hot-pressed member and manufacturing method therefor

    WO2016139953A1